2020
DOI: 10.1039/d0cc05316c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and applications of amino-functionalized carbon nanomaterials

Abstract: Carbon-based nanomaterials (CNMs) have attracted considerable attention in the scientific community both from a scientific and an industrial point of view. Fullerenes, carbon nanotubes (CNTs), graphene and carbon dots (CDs)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 201 publications
0
36
0
Order By: Relevance
“…One of the most common methods makes use of the standard EDC/NHS-catalyzed reaction, yielding the coupling of surface carboxyl moieties with amine groups into an amide bond (Figure 2(b1)) [116]. Notably, the same approach may be used when starting with N-doped C-dots, whose surfaces are usually decorated by amino groups and react with carboxyl-containing targets (Figure 2(b2)) [117].…”
Section: Carbon Dotsmentioning
confidence: 99%
“…One of the most common methods makes use of the standard EDC/NHS-catalyzed reaction, yielding the coupling of surface carboxyl moieties with amine groups into an amide bond (Figure 2(b1)) [116]. Notably, the same approach may be used when starting with N-doped C-dots, whose surfaces are usually decorated by amino groups and react with carboxyl-containing targets (Figure 2(b2)) [117].…”
Section: Carbon Dotsmentioning
confidence: 99%
“…The emerging nanocarbon materials with different dimensional nanostructures also bring opportunities for building metalcarbon composite catalysts with controllable spatial arrangements within a primary catalyst particle. [165,166] The optimum particle sizes of cobalt and iron for FT synthesis are generally smaller than 10 nm, and such small metal NPs are prone to aggregate due to the high surface energy. [72,92] Although the functional sites on carbon materials can stabilize the metal NPs to a great extent as discussed above, the utilization of structural features of carbon materials can further restrict the growth of metal NPs.…”
Section: Encapsulated Metal Catalystsmentioning
confidence: 99%
“…Moreover, in the following studies, we demonstrated that even nitrogen-doped carbon-based nanomaterials can serve as photocatalysts for the iodoperfluoroalkylation of organic compounds. [55][56][57] The mentioned purple light strategy was employed for the construction of a key intermediate in the synthesis of the breast cancer drug, namely Fulvestrant, in gram-scale (Method b, Figure 7).…”
Section: Iodoperfluoroalkylation Of Olefinsmentioning
confidence: 99%